Performing the Hyphen - Seifert (With Lime – Wellington, New Zealand), Miki (Revista Brasileira de Estudos da Presença, 2022)
The goal of this paper is to present a decolonising research methodology. The first section of this paper problematises western knowledge production, using Aníbal Quijano’s colonial matrix of power. The second section theorises how an epistemological pluralism that is critical, decolonising and performative could address western knowledge production and the colonial matrix of power. The third section discusses how this methodology has been applied to Butoh to develop Critical Butoh. The final section presents He rawe tona kakahu/ She wore a becoming dress, a Butoh performance exploring the intersection of gender and colonisation, as a practical application of this methodology.